Extracellular peptidases of the cereal pathogen Fusarium graminearum - Lowe, Rohan G. T.; McCorkelle, Owen; Bleackley, Mark; Collins, Christine; Faou, Pierre; Mathivanan, Suresh; Anderson, Marilyn (Frontiers in Plant Science, 2015)
The plant pathogenic fungus Fusarium graminearum (Fgr) creates economic and health risks in cereals agriculture. Fgr causes head blight (or scab) of wheat and stalk rot of corn, reducing yield, degrading grain quality and polluting downstream food products with mycotoxins. Fungal plant pathogens must secrete proteases to access nutrition and to breakdown the structural protein component of the plant cell wall. Research into the proteolytic activity of Fgr is hindered by the complex nature of the suite of proteases secreted. We used a systems biology approach comprising genome analysis, transcriptomics and label-free quantitative proteomics to characterise the peptidases deployed by Fgr during growth. A combined analysis of published microarray transcriptome datasets revealed seven transcriptional groupings of peptidases based on in vitro growth, in planta growth, and sporulation behaviours. An orbitrap MS/MS proteomics technique defined the extracellular proteases secreted by Fusarium graminearum. A meta-classification based on sequence characters and transcriptional/translational activity in planta and in vitro provides a platform to develop control strategies that target Fgr peptidases.